A Curious Case of Acute Respiratory Failure: Is It Antisynthetase Syndrome? - Gurveen Malhotra; Nitya Ramreddy; Serafin Chua; Mira Iliescu; Tanjeev Kaur (Case Reports in Critical Care)
Antisynthetase (AS) syndrome is a major subgroup of inflammatory myopathies seen in a minority of patients with dermatomyositis and polymyositis. Although it is usually associated with elevated creatine phosphokinase level, some patients may have amyopathic dermatomyositis (ADM) like presentation with predominant skin involvement. Interstitial lung disease (ILD) is the main pulmonary manifestation and may be severe thereby determining the prognosis. It may rarely present with a very aggressive course resulting in acute respiratory distress syndrome (ARDS). We report a case of a 43-year-old male who presented with nonresolving pneumonia who was eventually diagnosed to have ADM through a skin biopsy without any muscle weakness. ADM may be associated with rapidly progressive course of interstitial lung disease (ADM-ILD) which is associated with high mortality. Differentiation between ADM-ILD and AS syndrome may be difficult in the absence of positive serology and clinical presentation may help in clinching the diagnosis.